Sinonasal Malignancies – A Study of Demographic Profile, Disease Characteristics and Treatment Outcomes from a Tertiary Care Hospital in India - Divya Kukreja; Nirmal Kumar; Mrinalini Verma; Kirti Srivastava; Rajeev Gupta (NMO Journal)
Background: Sinonasal malignancies (SNMs) are rare and account for <0.2% of all cancers and about 3.6% of all malignancies arising in the head-and-neck region. We planned a retrospective analysis of this rare malignancy at our centre. Materials and Methods: The data were retrieved at the Department of Radiation Oncology between July 2019 and June 2024 and analysed for demographic profile, disease characteristics, stage at presentation, details of treatment received, compliance and outcomes. Results: Out of 108 patients with SNMs, 65% were male. The median age was 48.5 years. 68.5% of them had the primary disease in the maxillary sinus. Squamous cell carcinoma was the predominant histological type in 55.5% regardless of the site, followed by salivary gland tumour type in 13.9% of the patients. The lesion in the upper alveolus/palate was the most common presenting symptom, followed by epistaxis. Nearly all of them (91%) presented with locally advanced disease. Only 40% of patients were treated with curative intent, while the remaining patients were treated with palliative intent (chemotherapy and/or RT). At the time of data analysis, 7 (8.4%) patients were alive and disease-free, 24 (29%) patients were dead, 13 (15.6%) patients were alive with disease and the remaining 41% of patients were lost to follow-up. The median overall survival was 28.25 months (95% confidence interval: 6.67–49.83 months), irrespective of histology (P = 0.116). Conclusion: SNMs are a diverse group of tumours with varying histology and clinical profiles. As most of the patients present in advanced stages, their outcomes remain dismal irrespective of treatment strategies.